Heritage Crisis and the Current Changes in the Contemporary Arab Thought - AL-Shiyab, Mohammad (Jordan Journal of Social Sciences, 2020)
This paper attempts to show how contemporary Arab thought addressed heritage. It is evident that heritage is not part of contemporary Arab thought since there is a historical difference between the status quo and the past. Therefore, it was dealt with as detached from its circumstances and it was considered as metaphysics to assure its continuity and comprehensive validity. Metaphysics here indicates the abandon of the historic effect as factor in creating difference which, in turn, means the general difference between the Arab Islamic culture in the past (Heritage) and the status quo of culture (the present). The interest in heritage, accordingly, is an ill phenomenon which tries to resurrect the past. We started considering it as a fully- fledged independent entity that opposes the Arab present. This indicates that we see them as two different entities: The Arab heritage and the Arab present. Nonetheless, the real beginning of the contemporary Arab thought cannot be established but on an objective historic analysis of heritage and a historic analysis of the variable historic conditions that are capable of foreshadowing the questions of the Arab present.